Assessing High School Students' Creative Thinking Skills on Green Chemistry Material Using STEM-Based Creative Content Electronic Portfolios - Rahman M. Fiqri; Nahadi; .Siswaningsih W. (Postgraduate, University of Mataram, 2026)
This study aims to develop a valid and reliable STEM-based electronic assessment portfolio instrument to instill creative thinking skills in high school students on the topic of Green Chemistry. This study uses a Design Development Research (DDR) approach with the ADDIE model, which is specifically limited to the development phase. This study involved 16 grade 10 science students. The Assessment Portfolio was designed with three tasks: a summary of the Green Chemistry topic, a poster about the 12 principles of Green Chemistry, and an educational vlog about the principle of